Calf extra-Fascial compartment area affects calf muscle pumping action: an air plethysmography and computed tomography study. (June 2023) - Mitsuoka, Hiroki; Ohta, Takashi; Arima, Takahiro; Sugimoto, Ikuo; Orimoto, Yuki; Kodama, Akio; Ishibashi, Hiroyuki
Objectives: We aimed to elucidate whether lower limb extra-fascial compartment and muscle areas affect the calf muscle pumping action on lower limbs. Method: This study included 90 patients (180 limbs) who underwent preoperative air plethysmography (APG) and preoperative non-contrast computed tomography (CT) of the lower limbs for diagnosis of unilateral or bilateral primary varicose veins. A correlation between cross-sectional CT images and preoperative APG was confirmed. Cross-sectional CT was used to measure the extra-fascial compartment and muscle areas of the calf. The lower limbs were divided into two groups: those that were normal and those with primary varicose veins. Results: The extra-fascial compartment area was significantly correlated with the ejection fraction in normal (r = 0.388, n = 53, p = 0.004) and varicose limbs (r = 0.232, n = 91, p = 0.027). Conclusions: In normal and varicose limbs, evaluation of ejection fraction, an indicator of muscle pumping, requires consideration of the extra-fascial compartment area.